2020
DOI: 10.1002/qj.3949
|View full text |Cite
|
Sign up to set email alerts
|

Geostrophic drag law for conventionally neutral atmospheric boundary layers revisited

Abstract: The geostrophic drag law (GDL), which predicts the geostrophic drag coefficient and the cross‐isobaric angle, is relevant for meteorological applications such as wind energy. For conventionally neutral atmospheric boundary layers (CNBLs) capped by an inversion, the GDL coefficients A and B are affected by the inversion strength and latitude, expressible via the ratio of the Brunt–Väisälä frequency (N) to the Coriolis parameter (f). We present large‐eddy simulations (LES) covering a wider range of N/|f| than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…It is demonstrated that and are well parametrized by a function that depends only on , similar to what is observed in the classical GDL for flow over flat terrain (Zilitinkevich & Esau 2005; Liu et al. 2021 a ). This confirms that the similarity arguments apply for flow over extended wind farm arrays, even though their physics are different.…”
Section: Geostrophic Drag Law For Extended Wind Farmssupporting
confidence: 65%
See 1 more Smart Citation
“…It is demonstrated that and are well parametrized by a function that depends only on , similar to what is observed in the classical GDL for flow over flat terrain (Zilitinkevich & Esau 2005; Liu et al. 2021 a ). This confirms that the similarity arguments apply for flow over extended wind farm arrays, even though their physics are different.…”
Section: Geostrophic Drag Law For Extended Wind Farmssupporting
confidence: 65%
“…Typical values for the GDL coefficients and reported from meteorological observations are and (Hess & Garratt 2002). It has been shown that, for conventionally neutral ABLs, the coefficients and only depend on the Zilitinkevich number (Esau 2004; Kadantsev, Mortikov & Zilitinkevich 2021; Liu, Gadde & Stevens 2021 a , b ; Liu & Stevens 2022). Here is the free-atmosphere Brunt–Väisälä frequency, is the gravity acceleration, is the free-atmosphere lapse rate and is the reference potential temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The flow is initialized with uniform geostrophic wind speed and a linear potential temperature profile with a constant gradient [35,44]. The simulations are performed with an in-house code [50][51][52][53][54][55], which employs a pseudospectral discretization in the horizontal directions and a second-order finite difference method in the vertical direction. We employ the advanced anisotropic minimum dissipation model to parametrize the subgrid scale shear stress and potential temperature flux [56].…”
mentioning
confidence: 99%
“…For a detailed description and validation of our code we refer the reader to Refs. [31][32][33] The wind turbines are modeled using an actuator disk approach in which the free-stream velocity U ∞ is used to calculate the turbine force F wt…”
Section: A Numerical Methodsmentioning
confidence: 99%
“…Following Abkar and Porté-Agel [41], we first perform time-averaging of the filtered momentum equation [31][32][33],…”
Section: Kinetic Energy Budget Analysismentioning
confidence: 99%